Questionnaire survey of angiogenesis inhibitor-related oral complications based on a nation-wide study in Japan - Shin-ichi Yamada; Hiroshi Kurita; Akira Tanaka; Masaru Miyata; Yoshinari Morimoto; Akira Yamaguchi; Souichi Yanamoto; Hiromasa Yoshikawa; Yutaka Imai (Elsevier, 2021)
Background/purpose: The prevalence of oral adverse events and dental treatments related complications during the molecular targeted drugs therapy remains unclear. The purpose of this study was to investigate the contents of dental treatment-related complications in Japanese patients during molecular targeted therapy. Materials and methods: The nation-wide survey of dental treatment related complications was performed by the Japanese Society of Dentistry for Medically Compromised Patient as retrospective cohort study. Results: Among 212 dentists, 87.3% recognized the possibility of dental treatments related complications in patients with angiogenesis inhibitors. The oral adverse events including dental treatment-related complications associated with angiogenesis inhibitors were 79 cases. In patients with angiogenesis inhibitors, 73.4% of patients were administrated with bevacizumab. The average administration period of angiogenesis inhibitors was 14.0 ± 10.0 months. As the dental treatment related complications, delayed wound healing was most commonly seen in 45 patients (57.0%), followed by osteonecrosis of the jaw in 25 (31.6%). The triggered factor of complications was tooth extraction in 51 cases (96.2%). Conclusion: The extraction of the tooth with pre-existing inflammation may be suggested as one of risk factors for angiogenesis inhibitor-related dental treatment complications.